Pengaruh Motivasi Terhadap Prestasi Kerja Karyawan Studi Pada PT Pos Indonesia Tipe C Manado - Theodora Yatipai; John Montolalu; Sonny Gerson Kaparang (Universitas Sam Ratulangi, 2015)
Abstract: The purpose of this study was to determine the effect of motivation on employee performance of PT Pos Type C Manado. This research uses descriptive quantitative approach to measure and influence the relationship between motivation and job performance. The population in this study amounted to 200 employees, with a simple random sampling which amounts to 50 respondents. Using correlation and regression analysis. The analysis showed that there is a fairly strong correlation between motivation and job performance, as well as the motivation has a positive impact with work performance. Thus, the motivation has a strong relationship with the work performance of employees at PT Pos Indonesia Type C Manado.Keywords: Motivation, Job Performance